2019
DOI: 10.1016/j.heliyon.2019.e01172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organizational power networks through a holistic approach using consensus strategies

Abstract: Power is one of the most complex organizational attributes to understand due to the multiple related variables and dimensions in which it appears. The ownership and use and of power are reflected in the interpersonal relationships within an organization, as a result, modeling its structure and interactions can lead to knowledge about the power networks that shape it. The objective of this study was to identify the behavior of organizational networks based on existing sources of power, using a consensual analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Since social network analysis focuses on patterns of relationships between nodes, this method is particularly useful for investigating the structure of a network in terms of the relative importance of the nodes and the strength of their ties (Wasserman and Faust, 1994). Social network analysis techniques are increasingly being adopted to investigate social media networks, especially the connections and interactions between social media users or heterogeneous roles inside a network (Sedereviciute and Valentini, 2011; Himelboim et al., 2014; Ramos et al., 2019). In studies endorsing the social network analysis perspective, this approach is recognized to be “a natural form of understanding and evaluating public relations as it focuses on patterns of relationships among social entities” (Himelboim et al., 2014: 363–364).…”
Section: Resultsmentioning
confidence: 99%
“…Since social network analysis focuses on patterns of relationships between nodes, this method is particularly useful for investigating the structure of a network in terms of the relative importance of the nodes and the strength of their ties (Wasserman and Faust, 1994). Social network analysis techniques are increasingly being adopted to investigate social media networks, especially the connections and interactions between social media users or heterogeneous roles inside a network (Sedereviciute and Valentini, 2011; Himelboim et al., 2014; Ramos et al., 2019). In studies endorsing the social network analysis perspective, this approach is recognized to be “a natural form of understanding and evaluating public relations as it focuses on patterns of relationships among social entities” (Himelboim et al., 2014: 363–364).…”
Section: Resultsmentioning
confidence: 99%
“…However, the results obtained in the present investigation indicate that networks based on formal power have key nodes that coincide with the hierarchical position of the people in their organization. Studies such as that of Aalbers and Ipskamp (2012), Ramos et al (2019) and Taucean et al (2016) confirm this. Sutanto et al (2011 indicated that informal leaders appear more frequently in networks that reflect relationships that are also informal.…”
Section: Formal Power Network Present Significant Differences Considering the Hierarchies Within Each Organizationmentioning
confidence: 74%
“…Networks can be classified as formal or informal depending on the relationships between nodes. Formal networks refer to the relationships between nodes based on legitimate, reward or punishment power, having a direct relationship with the hierarchy that people occupy (Marineau, 2014;Norbom, 2010;Peir o and Meli a, 2003); and informal networks are when the relationships between nodes are based on referent and expert powers (Peir o and Meli a, 2003;Ramos et al, 2019). Formal leaders can be part of informal networks when the characteristics of the activities they perform are not necessarily planned or intentionally elaborated; thus, they are not a part of their formal roles (Hoppe and Reinelt, 2010;Sparrowe and Liden, 2005).…”
Section: Organizational Network and Leadershipmentioning
confidence: 99%
“…On the other hand, according to (Peiró & Meliá, 2003) power is bifactorial: it is either formal or informal. The first is provided by the structure (hence, organization) and the second by the relationships (Ramos et al, 2019). Concerning the organizational relations, power could be discussed inward or intra-organizationally and outward or inter-organizationally.…”
Section: Approaches To Studying Powermentioning
confidence: 99%